Climate finance strategies to reach the most vulnerable - Huyer, Sophia (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Building resilience with climate finance includes ensuring that income and investment opportunities reach vulnerable groups with targeted information, education, and finance. This includes financial literacy training and access to credit in small and affordable increments. Mobile money is one model: in Kenya 194,000 moved out of poverty, the majority female-headed households. Other models for accessible climate finance at the local level include farmers associations, women’s organizations and VSLAs (village savings and loans).